2014
DOI: 10.11604/pamj.2014.17.187.1911
|View full text |Cite
|
Sign up to set email alerts
|

Predictors to parental knowledge about childhood immunisation/EPI vaccines in two health districts in Cameroon prior to the introduction of 13-valent Pneumococcal Conjugate Vaccines (PCV-13)

Abstract: IntroductionPneumonia is vaccine-preventable, but the increasing death toll resulting from the disease in Sub-Saharan Africa is alarming. Several factors account for vaccine failing to reach every child, besides incomplete vaccine coverage. Most of these include the perceptions of parents/guardians and healthcare providers. Previous studies on the introduction of new vaccines have focused on experimental trials, coverage figures and vaccine efficacy in developed countries. Little is known on the factors which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…In a study designed to describe and analyze the socio-economic/demographic determinants and predictors to parental knowledge on immunizations, only 19% of those sampled were aware of the availability of the PCV-13. 67 This was in line with the study reported in Niger and Nigeria, with a low rate (4%) of knowledge about Oral Polio Vaccine (OPV) 66 and the low rate of awareness (1%) that measles was vaccine-preventable, respectively. 67 Health education, training, and refresher courses for healthcare workers on vaccination will ensure that women attending antenatal care get adequate information on vaccination.…”
Section: Women Educationsupporting
confidence: 87%
See 1 more Smart Citation
“…In a study designed to describe and analyze the socio-economic/demographic determinants and predictors to parental knowledge on immunizations, only 19% of those sampled were aware of the availability of the PCV-13. 67 This was in line with the study reported in Niger and Nigeria, with a low rate (4%) of knowledge about Oral Polio Vaccine (OPV) 66 and the low rate of awareness (1%) that measles was vaccine-preventable, respectively. 67 Health education, training, and refresher courses for healthcare workers on vaccination will ensure that women attending antenatal care get adequate information on vaccination.…”
Section: Women Educationsupporting
confidence: 87%
“… 67 This was in line with the study reported in Niger and Nigeria, with a low rate (4%) of knowledge about Oral Polio Vaccine (OPV) 66 and the low rate of awareness (1%) that measles was vaccine-preventable, respectively. 67 Health education, training, and refresher courses for healthcare workers on vaccination will ensure that women attending antenatal care get adequate information on vaccination. 68 …”
Section: Women Educationsupporting
confidence: 87%
“…We applied a retrospective case-finding observational study design using hospital registration data from the infectious disease surveillance sites hosted at the MCH in Yaoundé, Cameroon (Fig 1). As earlier described [13], the sites involved hospitals in both an urban and rural/semi-urban zones around Yaoundé, with a population of over 3.5 million inhabitants out of which 18% are children under-five [14].…”
Section: Methodsmentioning
confidence: 99%
“…Knowledge, attitude, and practice (KAP) survey is a method to reveal what specific groups of individuals know about certain topics and how they interact with them. KAP questionnaire has been extensively used by researchers in various health fields to evaluate the knowledge, attitudes, and practices of healthcare professionals [15][16][17], patients [18,19], and caregivers [20][21][22]. In audiology, KAP approach is commonly employed to investigate diverse hearing issues, including harmful noise exposure [23] and neonatal and preschool hearing screening [24,25].…”
Section: Introductionmentioning
confidence: 99%